Primary Epithelioid Angiosarcoma of Spleen: A Case Report and Review of Literature - Abdallah, Rania Abdallah (J Clin Diagn Res, 2016)
Splenic angiosarcomas are usually secondary tumours, and only few primary cases have been encountered. We report a unique primary case of epithelioid angiosarcoma arising in the spleen in a male patient 55-year-old and presented to our hospital as a medical emergency with acute abdomen and haemorrhagic ascitis. CT revealed splenic focal lesion and suggested that this abdominal haemorrhage was due to ruptured splenic haemangioma, thus abdominal exploration and splenectomy were done. The histopathological examination showed an infiltrating ill-defined growth formed of high grade epithelioid cells arranged in sheet-like growth pattern, with occasional papillary appearance. The presence of rudimentary vascular channels lined by epithelioid endothelial cells with occasional intraluminal erythrocytes suggested vascular tumour origin. The neoplastic cells showed diffuse expression of CD31 together with focal expression of cytokeratin (CK) and CD34. Because of its epithelioid morphology and unmistakable positivity for CK, this case may be easily misdiagnosed as a metastatic carcinoma, which is not uncommon finding in the spleen. Epithelioid angiosarcoma is a rare type of vascular tumour in the spleen, which co-expresses vascular and epithelial markers making its distinction from metastatic carcinoma is sometimes difficult.